Linking Employee Coaching, Team Commitment and Performance: Evidence from Indonesian MSMEs - Admiral; Chidir, Gusli; Asbari, Masduki; Supriatna, Heri; Novitasari, Dewiana (IJOSMAS, 2021)
This study investigates whether increased attention given to coaching practices affects performance, while considering the mediating effect of team commitment. Data were collected from 145 employees of a private manufacturing industry in Tangerang, Indonesia using quantitative methods and confirmatory surveys. This study shows that coaching has a positive and significant impact on employee performance, either directly or indirectly through team commitment mediation. The results of this study could have significant implications for HR managerial decision-making regarding the coaching practice process in the manufacturing industry employees in Indonesia. This study also helps the HR management of the manufacturing industry to seriously assess their HR development investment plans in the form of coaching practices and direct their company's HR strategic planning.